Odpowiedź :
Odpowiedź:
A) 2( x+4) +6x= 8
2x+8 +6x= 8
8x= 8-8
8x= 0
x=0
spr... 2*0 +8 +6*0=8
8=8
L=P
B) 5x- 2 ( x+4)= 10
5x-2x -8=10
3x= 10+8
3x= 18 /:3
x=6
spr... 5*6 -2*6 -8=10
30 -12 - 8 = 10
30-20=10
10=10
L=P
C) - 4 +4 ( 2-5x )= -9
-4 +8 -20x = -9
-20x= - 9 +4 - 8
-20x= -13
x= 13/20
Szczegółowe wyjaśnienie:
Odpowiedź:
A.
2(x+4)+6x=8
2x + 8 + 6x = 8
8x = 8 - 8
x = 0
B.
5x - 2(x+4) = 10
5x - 2x - 8 = 10
3x = 10 + 8 /:3
x = 18/3 = 6
C.
-4 + 4(2 -5x) = -9
-4 + 8 - 20x = -9
-20x = -9 - 4 /:(-20)
x = 13/20
Szczegółowe wyjaśnienie: